2018
DOI: 10.3389/fnhum.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sine Shaped High-Frequency Rhythmic Visual Stimuli Patterns for SSVEP Response Analysis and Fatigue Rate Evaluation in Normal Subjects

Abstract: Background: Recent EEG-SSVEP signal based BCI studies have used high frequency square pulse visual stimuli to reduce subjective fatigue. However, the effect of total harmonic distortion (THD) has not been considered. Compared to CRT and LCD monitors, LED screen displays high-frequency wave with better refresh rate. In this study, we present high frequency sine wave simple and rhythmic patterns with low THD rate by LED to analyze SSVEP responses and evaluate subjective fatigue in normal subjects.Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This is in agreement with the findings of our previous study on the comparison between the fatigue levels that simple and rhythmic single-message sinusoidal AM stimuli can cause (Shamsi et al, 2017). It is also in accordance with the results of previous studies on rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual stimuli that reduced the subjective fatigue, and confirms our second hypothesis. In addition, the insignificant and infinitesimal correlation between the fatigue and the psychological state can ensure us that the subjects truly reported the fatigue that was mainly caused by listening to the stimuli, regardless of their psychological status.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the findings of our previous study on the comparison between the fatigue levels that simple and rhythmic single-message sinusoidal AM stimuli can cause (Shamsi et al, 2017). It is also in accordance with the results of previous studies on rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual stimuli that reduced the subjective fatigue, and confirms our second hypothesis. In addition, the insignificant and infinitesimal correlation between the fatigue and the psychological state can ensure us that the subjects truly reported the fatigue that was mainly caused by listening to the stimuli, regardless of their psychological status.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, rhythmic stimulation modulates the intrinsic neural oscillatory characteristics (Treder et al, 2014;Herrmann et al, 2016) and facilitates keeping focus (Sato et al, 2019). Interestingly, it was revealed that rhythmic (Keihani et al, 2018b;Keihani et al, 2018a) and chaotic (Shirzhiyan et al, 2019) visual alongside auditory stimuli (Shamsi et al, 2017) brought about both enough distinguishable EEGs and less subjects' fatigue, compared to simple stimuli. Thus, rhythmic stimuli are one of the promising options for being used in aBCI.…”
Section: Introductionmentioning
confidence: 99%
“…The trigger output of g.USB Amp (start time of EEG recording) and the output of a Texas Instruments optical sensor (visual stimuli) were sent to National Instruments (NI) DAQ. Details of the signal recording setup are reported in our previous studies ( Keihani et al, 2018 ; Shirzhiyan et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to their high decoding accuracy, external stimuli such as periodic flickers are commonly used in VEP-based BCIs evoking steady-state visual evoked potentials (SSVEPs) ( Vialatte et al, 2010 ; Keihani et al, 2018 ). In SSVEP-based BCIs, the stimulus comprises a constant frequency that varies from low to high (1–100 Hz), which then leads to specific EEG responses that correlate with the stimulus frequency ( Vialatte et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation